2023
DOI: 10.3390/molecules28072939
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Biogenesis Regulator 1 Homolog (RRS1) Promotes Cisplatin Resistance by Regulating AEG-1 Abundance in Breast Cancer Cells

Abstract: Many ribosomal proteins are highly expressed in tumors and are closely related to their diagnosis, prognosis and pathological characteristics. However, few studies are available on the correlation between ribosomal proteins and chemoresistance. RRS1 (human regulator of ribosome synthesis 1), a critical nuclear protein involved in ribosome biogenesis, also plays a key role in the genesis and development of breast cancer by protecting cancer cells from apoptosis. Given that apoptosis resistance is one of the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Increased ribosome biogenesis is necessary to maintain the elevated proliferation rate of tumor cells [ 34 ]. Recent research has implicated RRS1 in the development of several malignancies and it is significantly upregulated in various tumors [ 35 , 36 , 37 , 38 ]. The results of our previous studies have demonstrated the function of RRS1 in the growth of BC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ribosome biogenesis is necessary to maintain the elevated proliferation rate of tumor cells [ 34 ]. Recent research has implicated RRS1 in the development of several malignancies and it is significantly upregulated in various tumors [ 35 , 36 , 37 , 38 ]. The results of our previous studies have demonstrated the function of RRS1 in the growth of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The GV492-GFP and GV115-EGFP lentiviral expression system (Shanghai GeneChem Co., Ltd.) was utilized for the transfection of cells expressing shRNA targeting RRS1 (sh-RRS1), control shRNA (sh-CON), scrambled control (OE-CON), and overexpressed RRS1 (OE-RRS1). The cells were subjected to infection with the corresponding lentiviruses at a multiplicity of infection (MOI) of 20 [ 37 , 38 ]. When the cells reached 20% to 30% confluence, they were transfected with the virus and Hitrans A&P (Shanghai GeneChem Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…126 GRP78 has been shown to play a key role in the mechanism of cancer growth. 127 GRP78, a crucial factor in the mechanism of cancer growth, is significantly downregulated by BBR in SW480 cells, leading to tumor inhibition and apoptosis. 128 Notably, reprogramming of lipid metabolism is a widely accepted hallmark of malignancy that affects the development of various tumors.…”
Section: Bbr Inhibits Crc Cell Proliferationmentioning
confidence: 99%